APLIKASI PREDIKSI STOK POPOK BAYI BERBASIS WEB DENGAN METODE TREND MOMENT - Budiana, Hernik Diah; Lestanti, Sri; Nur Budiman, Saiful (JATI (Jurnal Mahasiswa Teknik Informatika), 2022)
Sinar Makmur Supermarkets so far in determining the number of goods to be ordered to distributors still rely on intuition and work experience of employees, so there must be an application that can predict stock of goods. The method that can assist business owners in managing stock in stores is the forecasting method or prediction using the Trend Moment algorithm. This research includes development research using Trend Moment as an application development algorithm. The results of the Black Box test state that the functional requirements of the applications made can function properly with the results of application suitability of 95.83% and the normal level of 89.17% while the MAPE test results for baby diapers with types S40, M36, L32, XL28 and XXL24 respectively were 0.258%, 0.495%, 0.385%, 0.175% and 0.321%.